An Automatic Generation Method of Exploded View Based on Projection - Shao, Shuai; Xing, Yufei; Qu, Ligang; Li, Xin (Manufacturing Technology Journal, 2021)
Exploded view is a kind of schematic view which decomposes the assembly into parts and arranges according to certain rules to explain the product structural relationship and guide the relevant technical personnel to carry out product assembly or maintenance. It is necessary to consider the visibility constraints and explosion sequence rules to construct the exploded view. Manual creation will lead to repeated modification and low efficiency. In this paper, a projection based algorithm for automatic generation of exploded view is proposed. In this method, the explosion set of products is constructed based on disassembly matrix and the assembly sequence of complex products is represented as a set of ordered hierarchical exploded view, so as to ensure that the exploded view can clearly express the feasible assembly sequence. The projection interference detection method is proposed to ensure the visibility of the exploded view under a given angle of view, and the method of selecting the explosion direction is proposed to improve the compactness of the generated exploded view, and the explosion direction guideline is established to improve the readability of the exploded view. The algorithm has small storage space, fast search speed, and is not limited to a single specific perspective, so it is more general. The feasibility and efficiency of the algorithm are verified by an example of automatic generation of explosive drawing of fixture model.
Keywords: Exploded view；Projection；oriented bounding box(OBB)